ANXIETY, DEPRESSION AND STRESS RELATED TO QUALITY OF LIFE IN DENTISTRY STUDENTS AT A COLOMBIAN CARIBBEAN UNIVERSITY - Alpi, Stefano Vinaccia; Arrieta, Zulieth Lopez; Estrada, Luis David Hoyos; Berrio, Patricia Castellanos; Martinez, Melany Miranda; Puerta, Carolina Barrios; Zambrano, Maria Jose; Acosta, Veronica Benjumea (Revista Sistemática, 2025)
Introduction: Dentistry is a highly complex field; therefore, students are constantly subjected to significant mental and physical demands, in addition to other factors that generally affect university students. In this regard, it has been observed that some students experience difficulties during their academic training, which has translated into mental health disorders. Consequently, it is necessary for dental programs to be aware of the psychological state of their students to take appropriate action. Objective: To estimate the levels of anxiety, stress, and depression among students in the Dentistry Program at Universidad del Sinú, Colombia, during the process of acquiring clinical competencies, and to analyze their relationship with quality of life and well-being. Materials and Methods: This was an analytical observational study. Scales were used to measure stress, anxiety, depression, quality of life, and subjective well-being in dental students. Data analysis was performed using Spearman correlation for non-parametric data. Results: The SSP-14 scale identified that 10.66% of the students had low levels of stress, 88.6% moderate, and 1.69% high. The Spearman correlation did not show a significant relationship between quality of life and the other variables evaluated. Conclusion: The population of clinical practice dental students presents very high levels of stress, anxiety, and depression despite reporting a good quality of life.